Characterization of the complete chloroplast genome of Periploca sepium Bunge (Apocynaceae: Periplocoideae: Periploca), a traditional Chinese medicinal plant - Hua Rao; Zhan-Hui Song; Ru-Peng Cui; Qi-En Li; Jia-Bin Zou (Mitochondrial DNA. Part B. Resources, 2019)
Periploca sepium Bunge is not only a traditional medicinal plant, but also a pioneer species for soil and water conservation because of its great environmental adaptability. In this study, its complete chloroplast genome was assembled from the whole genome Illumina sequencing data. The circular genome was 153,513 bp in size, containing a large single copy (LSC) region of 83,818 bp and a small single copy (SSC) region of 18,177 bp, which were separated by a pair of 25,759 bp inverted repeat (IR) regions. It encoded a total of 139 genes, including 85 protein-coding genes, 46 tRNA genes, and eight rRNA genes. The most of gene species occurred as a single copy, while 15 gene species occurred in double copies. The overall A + T content was 61.9%, while the corresponding values of the LSC, SSC, and IR regions were 63.8, 68.1, and 56.6%, respectively. Phylogenetic analysis indicated that P. sepium was relatively close to the species belonging to the subfamily Apocynoideae.